Pharmacognostical Study of Bark of Shimshapa (Dalbergia sissoo Roxb) (International Journal of Ayurveda and Pharma Research, 2022)
Purpose: Pharmacognostical evaluation of bark of Dalbergia sissoo is done for identification in field and differentiates from other species of Dalbergia. Methods: Drug is studied taxonomically and its macroscopic, microscopic features were studied including powder microscopy of bark with suitable instruments. Results: Macroscopic study reveals on drying bark is flat curved inward with presence of cracks color reddish brown outer surface rough warty while inner surface was tough, longitudinally striated whereas microscopic study reveals outline of transverse section (TS) exposed rhytidome covering the upper part of section. It was continue with cork cells followed wide zone of secondarycortex. Concentric rings of fibres were present throughout the secondary phloem. The detailed TS showed dark coloured rhytodome cells followed by multilayered cork cells. Secretory cells containing tannin was present in secondary cortex zone. Presence of calcium oxalate crystals present in rays cells and parenchyma cells of cortex. Starch grains were present throughout the parenchyma cells. Powder was dark red in colour, bitter .taste , fruity odor. Powder microscopy reveals fragments of cork cells, stone cells, septate fibres, Pitted medullary ray cells, Prismatic crystals of calcium oxalate, simple starch grains and fragments of fibres found present. Conclusion: Finding of this study will falicitate pharmacognostic standardization of plant material and become an aid for identification as well as preparation of herbal monographs for the species and to enjoy the Ayuvedic classical claims.